CREATIVE ECONOMY BASED ON WASTE: “CIRCULAR ECONOMY ENTREPRENEURSHIP EDUCATION FOR STUDENTS AND COMMUNITIES IN ACEH TAMIANG” - T. Khairol Razi; Fairus; Safwan; Irfan; Fadli Syahputra (RADJA PUBLIKA, 2026)
Low public awareness and understanding of waste management with economic value. The ever-increasing volume of household and plastic waste has not been optimally utilized, thus creating environmental problems as well as lost economic opportunities for the community. On the other hand, students and the community in Aceh Tamiang still have limited knowledge and skills in processing waste into creative products that have sales value. The concept of a circular economy that emphasizes the reuse of waste into useful products is also not widely understood and applied in everyday life. Community service was carried out in Kota Lintang Village, Hasanah Hamlet, Kota Kuala Simpang District, Aceh Tamiang Regency, which was affected by flooding through an educational and participatory approach to students and the community from May 20 to 22, 2026. After receiving educational materials on the impact of plastic waste and the concept of 3R management (Reduce, Reuse, Recycle), there was a significant increase in participants' understanding of environmental issues. Through evaluations in the form of post-tests and discussion sessions, it was found that around 70% of participants were able to explain in a coherent manner the negative impact of plastic waste on the environment, the importance of reducing the use of single-use plastics, and the benefits of creative plastic waste processing. Regular mentoring for students and the community is needed to ensure that circular economy programs are not only educational but also provide sustainable business opportunities. Support from Adiwiyata partners, local governments, and universities is expected to strengthen the implementation of environmental and entrepreneurship programs, creating a more independent, creative, and environmentally conscious community